2016
DOI: 10.1371/journal.pone.0158032
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Linked to Autosomal Dominant Nocturnal Frontal Lobe Epilepsy Reduces Low-Sensitivity α4β2, and Increases α5α4β2, Nicotinic Receptor Surface Expression

Abstract: A number of mutations in α4β2-containing (α4β2*) nicotinic acetylcholine (ACh) receptors (nAChRs) are linked to autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE), including one in the β2 subunit called β2V287L. Two α4β2* subtypes with different subunit stoichiometries and ACh sensitivities co-exist in the brain, a high-sensitivity subtype with (α4)2(β2)3 subunit stoichiometry and a low-sensitivity subtype with (α4)3(β2)2 stoichiometry. The α5 nicotinic subunit also co-assembles with α4β2 to form a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…In comparison with wild-type littermates, V286L-TG rats display nicotine-induced abnormal motor activity, including seizures, whereas the response time for seizures after nicotine administration is shorter in V286L-TG rats than in the wild type [ 230 ]. Recently, it was discovered that a β2 mutant subunit (β2V287L) suppresses low-sensitivity expression of α4β2* nAChRs in KI mice and that α4β2* nAChRs might regulate nicotine addiction and brain reward and other behaviors [ 199 , 231 ]. The β2V287L mutation reduces the EC50 values of high and low sensitivity of α4β2 nAChRs to acetylcholine and suppresses low-sensitivity α4β2 expression by cognate agonists [ 231 ].…”
Section: Insight From Specific Rare Variations Of Nachr Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with wild-type littermates, V286L-TG rats display nicotine-induced abnormal motor activity, including seizures, whereas the response time for seizures after nicotine administration is shorter in V286L-TG rats than in the wild type [ 230 ]. Recently, it was discovered that a β2 mutant subunit (β2V287L) suppresses low-sensitivity expression of α4β2* nAChRs in KI mice and that α4β2* nAChRs might regulate nicotine addiction and brain reward and other behaviors [ 199 , 231 ]. The β2V287L mutation reduces the EC50 values of high and low sensitivity of α4β2 nAChRs to acetylcholine and suppresses low-sensitivity α4β2 expression by cognate agonists [ 231 ].…”
Section: Insight From Specific Rare Variations Of Nachr Subunitsmentioning
confidence: 99%
“…Recently, it was discovered that a β2 mutant subunit (β2V287L) suppresses low-sensitivity expression of α4β2* nAChRs in KI mice and that α4β2* nAChRs might regulate nicotine addiction and brain reward and other behaviors [ 199 , 231 ]. The β2V287L mutation reduces the EC50 values of high and low sensitivity of α4β2 nAChRs to acetylcholine and suppresses low-sensitivity α4β2 expression by cognate agonists [ 231 ]. Similar β2 subunit mutant effects were reported for two mutations (V287L and V287M) in the channel-lining M2 domain [ 199 ] and two mutations in the intracellular cytoplasmic loop C2 (V337G) [ 229 ].…”
Section: Insight From Specific Rare Variations Of Nachr Subunitsmentioning
confidence: 99%
“…First, it has been demonstrated in genetic studies and animal models of seizures that nAChR activity is altered in ADNFLE/SHE. [11][12][13][14] Moreover, a few authors have reported a significant antiseizure effect of transdermal nicotine patches in ADNFLE/SHE cases involving CHRNA4 15,16 or CHRNB2 17 mutations. This effect, partially observed in case 2, has mainly been attributed to a desensitization of nAChR resulting from therapeutic excessive exposure to nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…These early observations were confirmed partially by individual constructs or the pairwise expression of human α4β2 concatemers together with α4, β2, or α5 subunits in Xenopus oocytes; specifically (α4β2) 2 α5 receptors were as sensitive to ACh as (α4β2) 2 β2 receptors, while the concentration-response curve was significantly right-shifted for (α4β2) 2 α4 receptors compared to (α4β2) 2 β2 receptors (Tapia et al, 2007 ; Jin et al, 2014 ). More recently, Nichols and colleagues injected Xenopus oocytes with α5, α4, and β2 mRNA at a 10:1:1 ratio (i.e., a 10-fold excess of α5) and found that 100% of the receptors were high-affinity (i.e., α5 subunit-containing), with an ACh EC 50 of 0.26 μM); in contrast, oocytes injected with only α4 and β2 (at a 1:1 ratio) had a biphasic concentration-response, with 65% high-affinity receptors (ACh EC 50 : 0.67 μM) and 35% low-affinity receptors (ACh EC 50 : 190 μM) (Nichols et al, 2016 ).…”
Section: What We Already Know From Heterologously Expressed and Endogmentioning
confidence: 99%
“…As discussed above, Brown and colleagues found that deleting the α5 subunit in α5 KO mice significantly reduced DhβE-sensitive 86 Rb efflux in thalamic synaptosomes without affecting [ 125 I]-epibatidine binding, suggesting reduced receptor efficacy, rather than reduced expression of presynaptic receptors (Brown et al, 2007 ). Interestingly, Nichols and colleagues found that introducing the V287L mutation in the β2 subunit (a mutation linked to autosomal dominant nocturnal frontal lobe epilepsy) reduced the total surface expression of α4β2 * receptors expressed in HEK293 cells but caused a 4-fold increase in (α4β2) 2 α5 receptors at the plasma membrane (Nichols et al, 2016 ).…”
Section: What We Already Know From Heterologously Expressed and Endogmentioning
confidence: 99%